Triterpenoids Extracted From Antrodia cinnamomea Mycelia Attenuate Acute Alcohol-Induced Liver Injury in C57BL/6 Mice via Suppression Inflammatory Response - Liu, Yange; Wang, Zhuqian; Kong, Fange; Teng, Lesheng; Zheng, Xiaoyi; Liu, Xingkai; Wang, Di (Frontiers in Microbiology, 2020)
Excessive alcohol consumption causes liver injury-induced mortality. Here we systematically analyzed the structure of triterpenoids extracted from Antrodia cinnamomea mycelia (ACT) and investigated their protective effects against acute alcohol-induced liver injury in mice. Liquid chromatography-mass spectrometry and liquid chromatography with tandem mass spectrometry were performed to determine the structures of ACT constituents. Alcohol-induced liver injury was generated in C57BL/6 mice by oral gavage of 13 g/kg white spirit (a wine at 56% ABV). Mice were treated with either silibinin or ACT for 2 weeks. Liver injury markers and pathological signaling were then quantified with enzyme-linked immunosorbent assays, antibody array assays, and western blots, and pathological examinations were performed using hematoxylin and eosin staining and periodic acid-Schiff staining. ACT contains 25 types of triterpenoid compounds. A 2-week alcohol consumption treatment caused significant weight loss, liver dyslipidemia, and the elevation of alanine aminotransferase, aspartate aminotransferase, γ-glutamyl transferase and alkaline phosphatase activities in the serum and/or liver. These effects were markedly reversed after 2-week ACT administration. ACT alleviated the organ structural changes and inflammatory infiltration of alcohol-damaged tissues. ACT inhibited pro-inflammatory cytokine levels and enhanced anti-inflammatory cytokine levels. Acute alcohol treatment promoted inflammation with significant correlations to with hypoxia-inducible factor 1 alpha (HIF-1α), which was reduced by ACT and was partially related to modulation of the protein kinase B (Akt)/70-kDa ribosomal protein S6 kinase phosphorylation (p70S6K) and Wnt/β-catenin signaling pathways. In conclusion, ACT protected against acute alcohol-induced liver damage in mice mainly through its suppression of the inflammatory response, which may be related to HIF-1α signaling.